Physics ContributionModified Heyman packing performed with small number of Simon-Norman catheters - Pálvölgyi, Jenő; Agyemang-Prempeh, Kofi (Journal of Contemporary Brachytherapy, 2010)
Purpose: Modified Heyman packing method, performed usually with 6-11 flexible catheters is one out of many brachytherapy treatments. We described the insertion and dose planning method, with the use of 4-6 Simon-Norman catheters positioned to the fundus uteri, which is the most frequent source of the endometrial cancer. Material and methods: We investigated the dose distribution of the main classes of regular catheter insertions with Simon-Norman applicators using dose profiles, obtained in lateral and axial direction at the fundus, and compared with the dose distribution of the Y-shaped catheter arrangements. Results: The insertions with five and six Simon-Norman catheters produced higher dose at the fundus uteri, compared with the Y-shaped applicator. Conclusions: Insertions performed with small number of catheters permits to perform dosimetry optimisation for each treatment fraction.